High-throughput interrogation of immune responses using the Human Immune Profiling Pipeline - Wang, Guanning; Lyudovyk, Olga; Kim, Justin Y.; Lin, Ya-Hui; Elhanati, Yuval; Mathew, Divij; Wherry, E. John; Herati, Ramin S.; Greenplate, Allison R.; Greenbaum, Benjamin; Vardhana, Santosha A.; Huang, Alexander C. (STAR protocols, 2023)
The current abundance of immunotherapy clinical trials presents an opportunity to learn about the underlying mechanisms and pharmacodynamic effects of novel drugs on the human immune system. Here, we present a protocol to study how these immune responses impact clinical outcomes using large-scale high-throughput immune profiling of clinical cohorts. We describe the Human Immune Profiling Pipeline, which comprises an end-to-end solution from flow cytometry results to computational approaches and unsupervised patient clustering based on lymphocyte landscape. For complete details on the use and execution of this protocol, please refer to Lyudovyk et al. (2022).1 [Display omitted] •High-dimensional analysis and dimension reduction using UMAP•Earth Mover’s Distance (EMD) calculations to quantify differences in UMAPs•Unsupervised patient classification by EMD values•Cell type annotations and patient phenotyping on EMD groups Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. The current abundance of immunotherapy clinical trials presents an opportunity to learn about the underlying mechanisms and pharmacodynamic effects of novel drugs on the human immune system. Here, we present a protocol to study how these immune responses impact clinical outcomes using large-scale high-throughput immune profiling of clinical cohorts. We describe the Human Immune Profiling Pipeline, which comprises an end-to-end solution from flow cytometry results to computational approaches and unsupervised patient clustering based on lymphocyte landscape.